A consanguineous family with Hirschsprung disease, microcephaly, and mental retardation (Goldberg-Shprintzen syndrome). Issue 6 (1st June 1999) - Brooks, Alice S; Breuning, Martijn H; Osinga, Jan; Smagt, Jasper J vd; Catsman, Corine E; Buys, Charles H C M; Meijers, Carel; Hofstra, Robert M W
Abstract : Hirschsprung disease, mental retardation, microcephaly, and specific craniofacial dysmorphism were observed in three children from a large, consanguineous, Moroccan family. A fourth child showed similar clinical features, with the exception of Hirschsprung disease. The association of these abnormalities in these children represents the Goldberg-Shprintzen syndrome (OMIM 235730). Mutation scanning of genes potentially involved in Hirschsprung disease, RET, GDNF, EDN3, and EDNRB, showed a sequence variant, Ser305Asn, in exon 4 of the EDNRB gene in the index patient of this family. The Ser305Asn substitution present in two of the four patients and four healthy relatives and absent in one of the remaining two patients illustrates the difficulties in interpreting the presence of mutations in families with Hirschsprung disease. It is unlikely that the EDNRB variant contributes to the phenotype. This consanguineous family might be useful for the identification of a Goldberg-Shprintzen locus.